The Current Distribution of Carex alatauensis in the Qinghai–Tibet Plateau Estimated by MaxEnt - Yunfei Xing; Jianjun Shi; Kejia De; Xiaoli Wang; Wei Wang; Yuan Ma; Hairong Zhang; Miaohua He; Qingqing Liu (Agronomy, 2023)
Modeling the current distribution of and predicting suitable habitats for threatened species support the species conservation and restoration planning process. Therefore, the purpose of this study was to model the actual distribution and predict environmentally suitable habitats for Carex alatauensis S.R.Zhang 2015, a locally threatened native grass species on the Qinghai–Tibet Plateau. To realize this objective, based on the geographical samples within the natural distribution of C. alatauensis, the dominant climatic factors in its potential distribution range were analyzed using the maximum entropy (MaxEnt) model. The results showed that the average values of the area under the receiver operating characteristic curve (AUC) of the training data were 0.833 ± 0.044, which indicated that the accuracy of the MaxEnt model was pretty high for modeling potential distribution regions of C. alatauensis. The combined results from the Jackknife test and the presented contribution of environmental variables revealed that the annual precipitation, the growth season precipitation, and the precipitation of the driest month were the key climatic factors that restricted the distribution of C. alatauensis on the Qinghai–Tibet Plateau. It is predicted that the potential distribution area of C. alatauensis on the Qinghai–Tibet Plateau is 1.96 × 106 km2, and the most suitable area is 3.7 × 105 km2, mainly located in the Qilian Mountains, the Himalayas, and the Qingtanggula Mountains.